Valorization of phosphate mine waste rock as alternative aggregates for high-performance concrete - Yahya El Berdai; Yassine Taha; Romain Trauchessec; Yasmine Rhaouti; Amine el Mahdi Safhi; Rachid Hakkou; Mostafa Benzaazoua (Case Studies in Construction Materials)
Natural aggregate quarrying significantly impacts the environment while phosphate mine waste rock (PMWR) offers alternative aggregates for use in high-added value construction materials. This study was the first to investigate the application of three aggregate types from PMWR as a complete substitute to natural aggregate to produce high-performance concrete (HPC). For this aim, three coarse aggregate (CA) types: Flint (F), Phosflint (PF), and Dolomite (D) from PMWR in Morocco were selected and compared with a natural Reference CA (R). Two mixtures were tested: HPC-0.40 and HPC-0.36 with a w/c ratio equal to 0.40 and 0.36. D-HPC and PF-HPC achieved a slump exceeding 20 cm and a 28-d compressive strength (CS) equal to 55 MPa ± 5 MPa on average, similar to the R-HPC, while F-HPC did not meet the requirement for HPC (i.e. a 28-d CS superior to 55 MPa). Scanning electron microscope observations showed that D-HPC exhibited a very dense and indistinguishable interfacial transition zone (ITZ), while F-HPC showed a debonding of F-CA and a larger ITZ size which explain its lower CS. Life ycle assessment revealed a major positive environmental impact on ecosystem quality that reduced land occupation and land transformation by up to 32 %. A secondary evaluation of the valorization of PMWR as alternative fine aggregate (FA) in high-strength mortar (HSM) was investigated and showed that the 28-d CS is equal to 93 MPa for PF-HSM and equal to 81 MPa for D-HSM, superior to RS-HSM which is equal to 61 MPa. Dolomite and Phosflint FA offered a better alternative to natural River sand to overcome the ceiling effect. These findings encourage the construction sector to adopt a sustainable consumption of aggregates by using PMWR as alternative CAs and FAs to produce high-strength construction materials.